Residuos de plaguicidas organoclorados en tejido adiposo humano en Costa Rica - Barquero García, Mercedes (1986)
Organochlorine pesticide residues were found in 82 samples of human adipose material fram 82 surgical cases in 16 Costa Rica hospitals. Identification was made by gas-liquid chromatography. The highest pesticide concentration was that of DDT ant its metabolytes (33.16 μg/g). Residues of almost all commercial pesticides were also found. Concentrations of a-chlordanc. Aldrin and Polychlorinated biphenyls were not significant.